基于VB的三曲柄环板减速器设计计算软件开发 - 管锋; 周传喜; 骆广 (Jixie chuandong)
In order to design the new transmission device—three crank and ring reducer easily,the interface software about design and calculation is developed on the base of VB6.0.The software can be used for the design calculation of the three basic structure forms of this device,including single ring,double ring and three rings.Through combining VB language and 3D modeling software SolidWorks,the reducer design calculation is realized,the three dimensional parametric model of the main parts are achieved,and 2D working drawing of parts can also be generated.The development of the software for this kind of gear reducer has some significance for physical manufacturing.